(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Natural science is a subject that provides schoolchildren with a general understanding of the whole of existence, and it is important to teach this subject to elementary school students using various interesting games and effective teaching methods. This article provides detailed information about oral teaching methods that support the teaching of natural science.